Contemporary Tibetan Cosmology of Climate Change - Salick, Jan; Byg, Anja; Bauer, Kenneth (Journal for the Study of Religion, Nature and Culture, 2013)
Open-ended interviews with over 50 Tibetan experts on contemporary Tibetan cosmology of climate change reveal a breadth of interpretation of and belief about developing climatic conditions in the eastern Himalayas and in Lhasa. We group these interpretations into Buddhist, pre-Buddhist/shamanistic, and modern scientific/materialistic constructions. These categories overlap and combine broadly with individual interpretations to the point where neither Buddhists nor scientific scholars would recognize their disciplines. Nonetheless, generally, there are beliefs that the climate is changing, that bad deeds have caused this, and that good deeds will mitigate it (Buddhist), fickle gods must be supplicated and appeased (shamanist), or there are material causes and solutions (scientific/ materialistic). As in our previous quantitative study on perceptions of climate change (Byg and Salick 2009), Tibetans widely agreed that climate change is happening: temperatures are rising, mountain glaciers and snows are melting, tree and shrub lines are advancing, rains are more variable, and agriculture and health are suffering. In the extreme, some Tibetans feel that their traditional culture—food, clothing, livelihoods—is no longer adaptive and that, along with their political woes, Tibetan culture is also doomed by climate change. There is increasing appreciation by climate change scientists and policy makers that indigenous knowledge and participation is important for monitoring, adapting to, and mitigating climate change. However, scientists and conservationists must offer concomitant appreciation of and respect for indigenous cosmologies that are the matrices in which indigenous thought, knowledge, and management are embedded.